Transesterification of Palm Oil Catalyzed by CaO/SiO2 Prepared from Limestone and Rice Husk Silica - Sri Elfina; Kamisah Delilawati Pandiangan; Novesar Jamarun; Fejri Subriadi; Hafnimardiyanti Hafnimardiyanti; Roswita Roswita (Pandawa Institute, 2024)
In this study, CaO/SiO2 composites were prepared from rice husk silica (RH-SiO2) and limestone from a local company. The composites with different mass ratios of CaO to SiO2 (1:1, 1:2, 1:3, 1:5, and 1:10) were synthesized using the sol-gel technique and characterized using XRF, XRD, and SEM. The composites were then used as catalysts for the transesterification of palm oil, with the main purpose to investigate the effect of catalyst compositions on the percentage of conversion of the oil. The results of XRD and SEM confirm the existence of RH-SiO2 as an amorphous material, and CaO as crystalline material, while the composites are a mixture of amorphous and crystalline phases. The catalysts were then used in transesterification experiments and the percentage of oil conversion was calculated. To confirm the successful conversion of palm oil into fatty acid methyl esters, the products of the reactions were analyzed using GC-MS. The experimental results demonstrated that the composites prepared exhibit catalytic activity, with the highest conversion (60%) achieved using the catalyst with the CaO to SiO2 ratio of 1:3.